De l’enfermement à l’élimination. Quelques expériences de la prison toulousaine et leurs conséquences pénales (fin xviie-xviiie siècles) - Laura Garet (Criminocorpus)
Murderers, thieves, arsonists and rebels were all criminals who could be punished by exemplary elimination. However, those sentenced to death or life imprisonment were held in the prisons of the lower courts and then in those of the Parliament of Toulouse, which was responsible for deciding on the punishment. The sources that allow us to approach the men and women who were finally sentenced to permanent exclusion thus reveal multiple experiences of detention. From the various prisons as places of safety to the “quartier de force” as a sentence, this contribution aims to draw up a typology of confinement, its spaces and its targets in the Toulouse area in the last third of the Ancien Régime.